Fabrication of a PVDF membrane with tailored morphology and properties via exploring and computing its ternary phase diagram for wastewater treatment and gas separation applications - Ashtiani, S; Khoshnamvand, M; Číhal, P; Dendisová, M; Randová, A; Bouša, D; Shaliutina-Kolešová, A; Sofer, Z; Friess, K (RSC advances, 2020)
We report a simple approach for tailoring the morphology of poly(vinylidene fluoride) (PVDF) membranes fabricated using a nonsolvent induced phase separation (NIPS) method that sustains both the hydrophilic and hydrophobic properties. Various membrane structures, i.e. skin layers and whole membrane structures as well, were obtained via an experimental method based on the obtained and computed ternary phase diagram. The nonsolvent interactions with polymer solution resulted in the different forms and properties of a surface layer of fabricated membranes that affected the overall transport of solvent and nonsolvent molecules inside and outside the bulk of the fabricated membranes. The resulting morphology and properties were confirmed using the 3D optical profiler, SEM, FT-IR and XRD methods. The effect of binary interaction parameters on the morphology of the fabricated membranes and on their separation performance was tested using water/oil mixture and gas separation. Both hydrophobic and hydrophilic properties of PVDF showed the excellent durable separation performance of the prepared membranes with 92% of oil separation and the maximum flux of 395 L h-1 m-2 along with 120 min of long-term stability. CO2 separation from H2, N2, CH4 and SF6 gases was performed to further support the effect of tuned PVDF membranes with different micro/nanostructured morphologies. The gas performance demonstrated ultrahigh permeability and a several-fold greater than the Knudsen separation factor. The results demonstrate a facile and inexpensive approach can be successfully applied for the tailoring of the PVDF membranes to predict and design the resulting membrane structure.